What's a germ, Joseph Lister? : the medical mystery that forever changed the way we heal - Alexander, Lori (Clarion Books, an imprint of HarperCollins Publishers, 2023)
"In 1841, a quiet, curious boy who stuttered when nervous committed to becoming a surgeon--a profession then more feared than respected. Through study, persistence, and careful research, Joseph Lister proved that unsanitary conditions contribute to infections. Despite others scoffing at his ideas, Lister slowly changed the way all surgeons work, saving countless lives"--